Authentic Audiovisual Resources to Actualise Legal Interpreting Education - Crezee, Ineke; Burn, Jo Anna; Gailani, Nidar (MonTi Monografías de Traducción e Interpretación, 2016)
New Zealand Aotearoa is an English-medium country and a home to a high number of minority migrant groups speaking over 160 different languages. To cater to the needs of such a diverse population, the Interpreting and Translation Team at Auckland University of Technology has developed a language-neutral pedagogy using a range of innovative teaching methods. One method is the use of authentic audiovisual material incorporating extracts from murder trials to raise awareness of courtroom discourse in general, and lawyers’ questions in particular. The aim of this study was to ascertain to what extent audiovisual clips are beneficial in legal interpreter education. After viewing audiovisual clips, students posted their practice on the university website. These recordings were then de-identified and formative feedback was given by language-specific markers as per standard performance based criteria. Students’ evaluation and comments from pre- and post-intervention surveys were analysed and form the basis of a discussion.